2013
DOI: 10.4071/imaps.390
|View full text |Cite
|
Sign up to set email alerts
|

A 4H-SiC Bipolar Technology for High-Temperature Integrated Circuits

Abstract: AbstractÀA 4H-SiC bipolar technology suitable for hightemperature integrated circuits is tested with two interconnect systems based on aluminum and platinum. Successful operation of low-voltage bipolar transistors and digital integrated circuits based on emitter coupled logic (ECL) is reported from 278C up to 5008C for both the metallization systems. When operated on 215 V supply voltage, aluminum and platinum interconnect OR-NOR gates showed stable noise margins of about 1 V and asymmetric propagation delays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…After 3 hours of continuous operation, CG dropped by almost 1.4 dB as compared to its initial value. This performance degradation was permanent and persisted even when the mixer was cooled back to 25 • C. The onset of failure mechanism, due to the accelerated electromigration in the Al-based metallization system [18], is believed to be the cause of permanent performance degradation with time at 500 • C. The electromigration manifests as a permanent increase in the access and contact resistances of the BJT with time, which not only degrades g m but also increase the mismatch losses, therefore leading to a CG degradation. Consequently, the long-term reliability of the in-house SiC BJT based circuits at elevated temperatures requires stable metallization systems e.g.…”
Section: B Measurement Resultsmentioning
confidence: 99%
“…After 3 hours of continuous operation, CG dropped by almost 1.4 dB as compared to its initial value. This performance degradation was permanent and persisted even when the mixer was cooled back to 25 • C. The onset of failure mechanism, due to the accelerated electromigration in the Al-based metallization system [18], is believed to be the cause of permanent performance degradation with time at 500 • C. The electromigration manifests as a permanent increase in the access and contact resistances of the BJT with time, which not only degrades g m but also increase the mismatch losses, therefore leading to a CG degradation. Consequently, the long-term reliability of the in-house SiC BJT based circuits at elevated temperatures requires stable metallization systems e.g.…”
Section: B Measurement Resultsmentioning
confidence: 99%
“…Compared with the reported light n-type layer sheet resistance data, [18] R SH.n in our work is effectively reduced by optimization of the dose of light nitrogen implants. As temperature increases to 400 • C, the higher the doping concentration, the lower the dopant activation, and the ionized dopant concentration increase is compensated for by the mobility lowering, [19] therefore R SH.n gradually increases to 9.44 kΩ/ while R SH.n + swings to 0.48 kΩ/ . to 0.89%, which is dominated by the increase of R S/D .…”
Section: Device Fabricationmentioning
confidence: 99%
“…Reliability testing for the 11-stage ring-oscillator (RO) using SiC TTL PDK indicated that the RO frequency of oscillation decreased 16% after HT characterization [17]. The degradation in DC and transient measurements was permanent, due to the accelerated electro-migration in the Al-based metalization system [26]. The long-term reliability of the SiC ICs at elevated temperatures require stable metalization as reported in [27].…”
Section: Reliabilitymentioning
confidence: 99%